Solução analítica em condução de calor multicamada : aplicação em ferramentas revestidas - Oliveira, Gabriela Costa de (2015)
In this work a transient one dimensional thermal problem with multilayer was solved analytical by using the Green\'s functions (FG) method. This method was used because the boundary conditions vary with time and this discards the use os the separation of variables method. The temperature prole for a two-layer medium was obtained and checks up this analytical solution by comparison with exact and numerical solutions of related thermal problems with specic characteristics. One important application of double layer solutions are given by thermal analysis in a coating machine tool. Accordingly, two analyzes of the thermal behavior of coated tools are addressed. Check up the thermal and geometric parameters involved, which allow a better distribution of temperature in the cutting area, reducing wear used in the process and to increase the tool life. It has been shown that coating with the thermal properties of the cobalt material, had an increase in temperature, while the coating of aluminum oxide (Al203) and titanium nitride (TiN) showed a decrease of temperature in the tool-coating interface.